A new approach to the upgrading of the traditional propylene carbonate washing process with significantly higher CO2 absorption capacity and selectivity. (15th April 2019) - Chen, Wan; Chen, Mengzijing; Yang, Mingke; Zou, Enbao; Li, Hai; Jia, Chongzhi; Sun, Changyu; Ma, Qinglan; Chen, Guangjin; Qin, Huibo
Highlights: The traditional PC washing approach was improved by adding mIm to PC with the presence of EG as cosolvent. CO2 solubility increases rapidly while those of CH4, N2 and H2 decrease drastically in the presence of mIm. Viscosity and absorption heat could remain on low level for EG-mIm-PC complex solvents. The selectivity of CO2 over CH4, N2 and H2 could be increased significantly using EG-mIm-PC complex solvents. Abstract: Although a series of advanced technologies and materials, like ionic liquids and metal organic frameworks, is being developed for carbon capture, traditional techniques, like propylene carbonate (PC) washing, are still widely applied in industry because of their low material costs and ease of operation. Considering the low CO2 solubility and selectivity in PC, we have tried to improve the PC washing process by adding 2-methylimidazole (mIm) to PC in the presence of ethylene glycol (EG) as cosolvent. A series of EG-mIm-PC complex solvents was prepared and their viscosities measured at different temperatures. The absorption isotherms of CO2 in these complex absorbents, as well as in pure PC, were measured at 293.15, 303.15, and 313.15 K at 0.1–0.8 MPa. The heats of CO2 absorption in these solvent mixtures were calculated using the Clausius-Clapeyron equation. For evaluating the effect of mIm on the selectivity of CO2 over other gas species, the absorption isotherms of CH4, N2, and H2 in pure PC and in 24%-mIm complex solvent with highest CO2 solubility were also measured. The results showed that the viscosities of these complex absorbents, as well as the solubility and heats of absorption of CO2 in all of them, moderately or slowly increased with an increase in mIm mass fraction, when the mIm content was lower than 20 wt%, and rapidly increased when it surpassed 20 wt%. The CO2 solubility could be more than doubled when the mIm content reached 24 wt% while viscosity and absorption heat still remains at low levels, that is, lower than 14 mPa·s and 26 kJ/mol, respectively. More importantly, the solubilities of CH4, N2, and H2 drastically decreased in the presence of mIm; using the 24 wt%-mIm complex absorbent instead of pure PC, the selectivity of CO2 over those other gas species increased by: 0.7–2.8 times for CH4, 3.9–6.3 times for N2, and 3.5–7.7 times for H2, with more significant improvements at lower pressure ranges. This work presents a very promising approach to PC washing technology upgrading.